Substansi dan Formal Bentuk Usaha Tetap (BUT) Pada Strategi Pengurangan Pajak - Muhammad Rifky Santoso (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
With a self-assessment system in carrying out taxation obligations, the tax authority must conduct atax audit so that the tax reduction strategies conducted by taxpayers can be detected and tax revenues can be received optimally. Taxpayers have the aim of maximizing profits by reducing tax payments. The lack of tax regulations in determining permanent establishment (PE), associate enterprises (related party), and elaboration of double taxation avoidance agreements or tax treaty (P3B), can be used by taxpayers, especially taxpayers from abroad for reducing tax payments in Indonesia. By using a case study in the Tax Court Decision in Indonesia, it is easily seen that foreign taxpayers implement strategies for tax reduction. By disguising BUT as a business relationship with an independent party, branch profit tax can be avoided and expenses for head office can be a way of reducing taxes and transferring profits abroad. Lack of information possessed by tax authorities regarding taxpayers and incomplete tax regulations, making taxpayer businesses in tax reduction cannot be prevented or reduced optimally. Efforts should be made to complete regulations especially those relating to BUT if there are transactions that are substantially BUT but formally not BUT, and associate enterprises due to the use of technology, as well as the translation of a tax treaty, especially terms that have not been explained in P3Ba tax treaty, such as the term 'control'.